“Proyecto de rehabilitación arquitectónico patrimonial, caso Colegio La Salle de la ciudad de Riobamba, provincia de Chimborazo” - Morocho Gonzáles, Fausto Nicolás (2016)
It is real that in the Ecuadorian and Latin American environment, where, in general their historical centers and buildings considered within the cultural heritage, are affected and threatened because of several reasons. The users’ lack of knowledge and the current economic dynamics, such as the increase in the number of houses and buildings, favor the rapid partial and total destruction of the cultural heritage built. The building under study in this research is the principal construction in La Salle Educational Unit which is 100 years old and is located within the inventory of cultural heritage in Riobamba. This building for several reasons is affected in its construction elements and spaces. These factors are easily identified, such as high frequency of use, anti-technical interventions, weather and external conditions. For the reasons aforementioned, an architectural rehabilitation project for the building was proposed; through the methodological theoretical framework determined in the research, the damage of the building was identified in order to define their causes and interventions; finally, after considering the change of use and the conservation of the cultural heritage, a project with the purpose of protecting this valuable building was developed.